PERANCANGAN ILUSTRASI GERAK BERGAYA GAMBAR SEMI REALIS SEBAGAI TEROBOSAN PRODUK BARU FARARAFA STUDIO - Zulfikar, Melsha Haq; Prasetiya, Happy Yugo (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2022)
This study discusses how to design motion illustrations with a semi-realist art style as a new product breakthrough for Fararafa Studio. The product in this study is an updated design from the previous product, namely an illustration image with a JPG extension. The purpose of this research is to produce a work process that can underlie the production process of motion illustrations with GIF and MP4 output as a product sample for Fararafa Studio and to test the feasibility of the illustration products that have been made by researchers. Using a Research and Development Methodology whose application is very suitable for testing the effectiveness of products with various stages and validations. The illustration will use a semi-realist drawing style because this semi-realist illustration product is the most sought after by Fararafa Studio's clients. The image process will use Adobe Photoshop software, then be animated using Adobe After Effects.